Characterization of a circular 80 mm anode supported solid oxide fuel cell (AS-SOFC) with anode support produced using high-pressure injection molding (HPIM). (19th July 2019) - Kupecki, Jakub; Kluczowski, Ryszard; Papurello, Davide; Lanzini, Andrea; Kawalec, Michał; Krauz, Mariusz; Santarelli, Massimo
Abstract: The current study was oriented at analyzing the performance of an anode-supported solid oxide fuel cell produced using high-pressure injection molding. The cell with a total thickness of 550 μm was produced in the Ceramic Department (CEREL) of the Institute of Power Engineering in Poland and experimentally analyzed in the Energy Department (DENERG) of Politecnico di Torino in Italy. The high-pressure injection molding technique was applied to produce a 500 μm thick anode support NiO/8YSZ 66/34 wt% with porosity of 25 vol%. The screen printing method was used to print a 3 μm thick NiO anode contact layer, 7 μm thick NiO/8YSZ 50/50 wt% anode functional layer, 4 μm thick 8YSZ dense electrolyte, 1.5 μm thick Gd0, 1 Ce0, 9 O2 barrier layer and a 30 μm thick La0, 6 Sr0, 4 Fe0, 8 Co0, 2 O3–δ cathode with porosity 25 vol%. The experimental characterization was done at two temperature levels: 750 and 800 °C under fixed anodic and cathodic flow and compositions. The preliminary studies on the application of high-pressure injection molding are discussed together with the advantages of the technology. The performance of two generations of anode-supported cells is compared with data of reference cells with supports obtained using tape casting. Highlights: The batch of anode supported cells solid oxide fuel cells was produced. High pressure injection molding was used for fabrication of the supports. Cells were laser cut to circles with diameter of 80 mm. Electrochemical performance of the cell was investigated at 750°C and 800°C. Performance of the cell is comparable to the one of commercial cells produced using tape casting.